Compliance of Iron and Folic Acid Supplementation among Postpartum Urban Mothers of Kathmandu Valley - Bhatt, Laxman Datt; Pal, Laxmi; Dhami, Shankar Singh; Thapa, Kanchan (Journal of Nepal Paediatric Society, 2021)
Introduction: Globally, iron deficiency anaemia is considered as a risk factor for maternal morbidity and mortality. It is estimated to cause 591,000 perinatal deaths and 115,000 maternal deaths annually. The World Health Organisation recommends iron supplementation to first trimester to 45 days after delivery. The Government of Nepal is supplementing Iron and Folic Acid (IFA) to pregnant and postpartum women to reduce the burden of disease and deaths, however Nepal reports low compliance and coverage. We sought to determine compliance of IFA and associated factors among postnatal mothers in Kathmandu valley. Methods: This was a cross-sectional study involving 132 mothers attending the immunisation clinic. Face to face interview was done using structured questionnaire consisting of sociodemographic information, IFA, maternal knowledge and compliance practices. Statistical analysis was done using SPSS version 23. Results: We found 68.9% compliance of iron and folic acid among the respondents. The mean age of the respondents was 27.53 ± 4.6 years (Mean ± SD). Significant association was observed between the compliance of the IFA with education,age,employment status of women and family type (p < 0.00). No significant association was observed in between the compliance of IFA and religion (p = 0.93) and delivery related complications (p = 0.143). Similarly, delivery type showed significant association with the compliance of IFA (p < 0.00). Conclusions: This study concludes that mothers from Kathmandu had better compliance and coverage of IFA than provincial as well as the national average. Private pharmacy is an important service provider for urban women.